Predicting Multicomponent Adsorption Isotherms in Open‐Metal Site Materials Using Force Field Calculations Based on Energy Decomposed Density Functional Theory. Issue 50 (2nd November 2016) - Heinen, Jurn; Burtch, Nicholas C.; Walton, Krista S.; Fonseca Guerra, Célia; Dubbeldam, David
Abstract: For the design of adsorptive‐separation units, knowledge is required of the multicomponent adsorption behavior. Ideal adsorbed solution theory (IAST) breaks down for olefin adsorption in open‐metal site (OMS) materials due to non‐ideal donor–acceptor interactions. Using a density‐function‐theory‐based energy decomposition scheme, we develop a physically justifiable classical force field that incorporates the missing orbital interactions using an appropriate functional form. Our first‐principles derived force field shows greatly improved quantitative agreement with the inflection points, initial uptake, saturation capacity, and enthalpies of adsorption obtained from our in‐house adsorption experiments. While IAST fails to make accurate predictions, our improved force field model is able to correctly predict the multicomponent behavior. Our approach is also transferable to other OMS structures, allowing the accurate study of their separation performances for olefins/paraffins and further mixtures involving complex donor–acceptor interactions. Abstract : A super model : Ideal adsorbed solution theory breaks down in open‐metal site materials due to non‐ideal donor–acceptor interactions. Kohn–Sham molecular orbital theory can explain these donor–acceptor interactions, and by incorporating these interactions into a force field model, the multicomponent adsorption behavior can be accurately predicted.